Local and post local buckling of hollow and concrete filled box steel tubes - Omar Saber Rizq Hassan; Ahmed Foad Sabry; Kamal Ghamry Metwally (Cairo : Omar Saber Rizq Hassan, 2016)
This research studies the local and post local buckling behavior of hollow and concrete filled box steel tubes. ANSYS program is used to model the specimens. The critical stresses and buckled shapes of ANSYS are compared to their corresponding results of experiments and mathematical solution. Eighty four models are implemented to conduct the parametric study which determined the effects of section slenderness ratio b/t ,yield strength of steel tube, and concrete infill on initial buckling stress vL, post local buckling stress vu, non dimensional critical stress vL/ vy, and reserve strength vr which is gained due to the post local buckling
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Civil Engineering
Issued also as CD
Keywords: Concrete Filled Steel Tube (CFT); Hollow steel section; Local buckling